A new genus and species of whiptail armored catfish (Siluriformes: Loricariinae) from southern Venezuela - Provenzano-Rizzi, Francisco (Zootaxa, 2023)
A new genus and species of whiptail loricariid catfish belonging to the Pseudohemiodon group is described with 12 specimens captured from the upper Orinoco River and Casiquiare River, Amazonas State, Venezuela. The specimens show delicate and fragile appearance, and are small (largest specimen 74.3 mm SL). The new species has external morphological characters that support its inclusion in the Pseudohemiodon group; however, its mouth morphology is distinctive and unique with features not observed in any species of that group, nor in any other species included in tribe Loricariini or in subfamily Loricariinae. The distinctive buccal characters include: 1) barblets on upper lip border and the maxillary barbel included and interconnected by translucent membrane, leaving the tips free; 2) lower lip surface covered with elongated, cylindrical, unbranched, and fleshy barblets, which resemble filaments, some of them surpassing the border of lower lip. The comparative analyses carried out determined that the recently described species Rhadinoloricaria papillosa has the same two diagnostic buccal characters observed in the new species; therefore it is transferred to the new genus.